Cross-cultural validation of the Retinopathy Treatment Satisfaction Questionnaire status version (RetTSQs) in Serbian community: a cross-sectional study. Issue 1 (19th January 2020) - Karadzic, Jelena; Stojkovic, Milenko; Risimic, Dijana; Bozic, Marija; Slijepcevic, Nikola; Polovina, Snezana; Grgurevic, Anita
Abstract : Objective: Cross-cultural translation and validation of the Serbian version of the Retinopathy Treatment Satisfaction Questionnaire status version (RetTSQs). Design: Cross-sectional study. Settings: The study was conducted between June 2017 and June 2018 at tertiary care centre in Serbia, Belgrade. Participants: A total of 101 patients with diabetic retinopathy (DR) were included. All subjects were evaluated in two consecutive visits, the first during the initial contact to the clinic, while the second 4–6 weeks later. Main outcome measures: Validation of Serbian version of the RetTSQs was the major outcome. Results: Cronbach alpha coefficient of the subscales ranged from 0.783 (positive scale) to 0.811 (negative scale) and for all domains it was excellent at α=0.829. The intraclass correlation coefficient was greater than 0.8 for all of the subscales. Univariable analyses revealed that age, gender, education, marital status and working status did not affect the RetTSQ scores, whereas participants with non-proliferative DR reported signiﬁcantly higher treatment satisfaction (TS) than those with proliferative retinopathy (p=0.001). The group who received laser treatment scored signiﬁcantly lower than the group without it (p=0.004) regardless of type of performed laser. Positive and statistically significant correlations were found between the RetTSQ score and most of the National Eye Institute Visual Functioning Questionnaire-25 subscales. Conclusion: Translated Serbian adaptation of the RetTSQs showed adequate psychometric characteristics as an acceptable, reliable and valid questionnaire. It was well understood by Serbian diabetic patients and it promises to be used in daily clinical work as an instrument for the assessment of TS for patients with DR.